2006
DOI: 10.1007/s11292-006-9020-y
|View full text |Cite
|
Sign up to set email alerts
|

Are counter-terrorism strategies effective? The results of the Campbell systematic review on counter-terrorism evaluation research

Abstract: The events of September 11th have led to massive increases in personal, commercial, and governmental expenditures on anti-terrorism strategies, as well as a proliferation of programs designed to fight terrorism. These increases in spending and program development have focused attention on the most significant and central policy question related to these interventions: Are these programs effective? To explore this question, this study reports the results of a Campbell Collaboration systematic review on evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(101 citation statements)
references
References 29 publications
1
97
0
3
Order By: Relevance
“…This has severely limited the ability of policy-makers to develop and implement effective prevention and intervention strategies (Lum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This has severely limited the ability of policy-makers to develop and implement effective prevention and intervention strategies (Lum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have already found that metal detectors and screening at airports can reduce the occurrence of airplane hijacking ( Landes, 1978 ;Cauley and Im, 1988 ;Enders et al , 1990 ;Sandler, 1993, 2000 ; see also Lum et al , 2006 ). This is not surprising, given that the prevention mechanism behind metal detectors is theoretically well-developed and empirically supported.…”
Section: The Procedural Fairness Of Airport Security Screeningmentioning
confidence: 94%
“…Large quantities have been directed for the creation of government agencies like the Deparment of Homeland Security (DHS), the restructuring of the Department of Defense with the conformation of the Northern Command (Northcom which is in charge of the territory defense of countries like the U.S., Canada, Mexico, and part of the Caribbean), and the reordering of the Federal Bureau of Investigation (FBI) [12]; also for improving airport and border security, increasing research on response to biological or chemical agents, creating new laws, improving medical response for emergencies, providing help to other countries [13], and creating programs to reduce terrorism by strengthening potential objectives (e.g. reinforcing airport security control, placing barricades around buildings, or improving security for diplomats [14]).…”
Section: Literary Reviewmentioning
confidence: 99%